(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Lower genital tract infections (LGTIs) and urinary tract infections (UTIs) are common among pregnant women due to physiological, hormonal, and anatomical changes during pregnancy [1]. These infections are associated with adverse maternal and neonatal outcomes, including anemia, preterm labor, low birth weight and neonatal infections [2]. Early diagnosis and appropriate management are essential to reduce pregnancy-related complications and improve maternal health outcomes [3]. Objective: To study the common causes of infectious vaginitis in pregnancy and to determine the risk of Urinary Tract Infections in pregnant women with bacterial vaginosis in a tertiary care hospital. Methods: This cross-sectional study was conducted at Government tertiary care hospital in Chennai ,Tamilnadu for a period of one year. Results: Among 200 antenatal women, the prevalence of infectious vaginitis was 32.5%, most commonly affecting women aged 26–30 years. Bacterial vaginosis (21%) was the predominant infection, followed by vulvovaginal candidiasis (11.5%). UTIs were observed in 16% of patients, with higher prevalence in the third trimester. A significant association was found between bacterial vaginosis and UTI (p<0.05), whereas vulvovaginal candidiasis showed no significant association. Multidrug resistance was observed in 33% of urinary isolates. Candida albicans was the most common Candida species isolated, while C.tropicalis was the only Candida non albicans species isolated from urine specimens and was sensitive to all azoles and Nystatin B. Conclusion: Bacterial vaginosis is the most common cause of vaginitis among pregnant women associated with adverse pregnancy outcomes. Routine screening and early treatment of vaginitis and UTIs during antenatal care may help reduce maternal and perinatal complications. The increasing prevalence of multidrug-resistant urinary isolates highlights the importance of culture-based diagnosis and judicious antibiotic use.